Planar Bragg grating in bulk Polymethylmethacrylate - Rosenberger, M.; Koller, G.; Belle, S.; Schmauß, Bernhard; Hellmann, R. (Optics Express, 2012)
We report on a one-step writing process of a planar waveguide including a Bragg grating structure in bulk Polymethylmethacrylate (PMMA). A KrF excimer laser and a phase mask covered by an amplitude mask were used to locally increase the refractive index in PMMA and thereby generate simultaneously the planar waveguide and the Bragg grating. Our results show a reflected wavelength of the Bragg grating of about 1558.5 nm in accordance to the phase mask period. The reflectivity of the grating is about 80%. Initial characteristics of the Bragg grating structure towards humidity are investigat
lhft_intern.bib::Rosenberger2012a